2009
DOI: 10.1002/lary.20118
|View full text |Cite
|
Sign up to set email alerts
|

Identification of distant metastases with PET‐CT in patients with suspected recurrent head and neck cancer

Abstract: A significant number of patients with recurrent HNSCC have distant metastases at the time of recurrence. These data suggest that PET-CT improves detection of metastatic disease in the high-risk patient and should be performed as part of the routine evaluation of patients with suspected recurrence prior to salvage surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 19 publications
2
30
1
Order By: Relevance
“…Fifth, the sensitivities in the HSROC curves for the included studies were not uniformly high. Nine (22%) of the 41 included studies had sensitivities of less than 75% (5,10,11,13,19,21,24,25,32). No clear reason for the large difference between these studies and other studies was found.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Fifth, the sensitivities in the HSROC curves for the included studies were not uniformly high. Nine (22%) of the 41 included studies had sensitivities of less than 75% (5,10,11,13,19,21,24,25,32). No clear reason for the large difference between these studies and other studies was found.…”
Section: Discussionmentioning
confidence: 81%
“…Head and Neck Cancer. When we considered all 16 studies (1,800 patients) with data on head and neck cancer (1,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), the pooled sensitivity, specificity, PLR, and NLR of 18 Lung Cancer. When we considered all 5 studies (578 patients) with data on lung cancer (22)(23)(24)(25)(26), the pooled sensitivity, specificity, PLR, and NLR of 18 Breast Cancer.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The use of pre-treatment FDG-PET/CT is advocated by many centers 1113. FDG-PET/CT has been shown to effectively diagnose second primary tumors and distant metastasis in HNSCC patients 1216.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of PET and CT will provide more anatomic details for the PET images, which is considered the most valuable imaging modality for the overall assessment of distant metastasis in patients with HNSCC (sensitivity: 88.8%; specificity: 95.1%) . Although many PET‐CT studies have been done, there has been no consensus with regard to the role of 18 FDG PET‐CT for diagnosis of lung malignancies in patients with HNSCC . Therefore, a meta‐analysis aiming to evaluate the diagnostic value of 18 FDG PET‐CT is urgently needed.…”
Section: Introductionmentioning
confidence: 99%